Low-temperature sodium ion battery and preparation method thereof
By optimizing the design of electrolytes and electrode materials, the problem of insufficient charging function and poor overall performance in sodium ion batteries in low -temperature environments, and achieve higher low temperature charging discharge performance and cycle stability.
Patent Information
- Application Number
- CN202411355498.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Sodium ion batteries exhibit insufficient charging function, low discharge capacity and poor overall performance in low temperature environments, limiting their application in cold areas.
By designing an optimized electrolyte, including NAFP6, NAFSI, carbonate ethyl ethylene, fluorodate carbonate, sulfate, 1,3 propyl, sodium diofluorophosthide, and organic solvents, and specific The positive and negative electrode materials, including sodium nickel perminnate, hard carbon and glue diaphragm, optimize the structure of the electrode and septum, shorten the ion transmission channel and increase the contact between the electrode and the diaphragm.
It significantly improves the charging and discharge performance, cycle stability and energy density of sodium ion batteries at low temperature, making it more suitable for high altitude and cold areas.
Smart Images

Figure BDA0005063499180000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries and relates to a low-temperature sodium ion battery and a preparation method thereof. Background Art
[0002] As an ideal candidate for the next generation of large-scale energy storage devices, sodium-ion batteries have attracted widespread attention due to their low cost. However, the practical utility of sodium-ion batteries is significantly limited by geographical and environmental factors, especially in high altitudes and cold regions. In these low-temperature environments, sodium-ion batteries face a series of severe technical challenges. First, the kinetics of electrochemical reactions under low temperature conditions become extremely slow, which directly affects the charge and discharge efficiency of the battery. Secondly, the stability of the electrode-electrolyte interface decreases significantly at low temperatures, resulting in an increase in interfacial resistance, further deteriorating the overall performance of the battery. In addition, the diffusion rate of sodium ions in electrode materials is greatly slowed down, especially in negative electrode materials, which not only reduces the energy density of the battery, but also may cause serious safety problems such as internal short circuits. These factors work together to greatly reduce the performance of sodium-ion batteries in low-temperature environments and cannot meet the needs of practical applications.
[0003] Faced with these challenges, researchers are actively exploring new solutions, among which the rational design of electrolytes and electrode materials is seen as the key to optimizing the low-temperature performance of sodium-ion batteries. For example, by adjusting the composition of the electrolyte and introducing specific additives, the freezing point of the electrolyte can be effectively lowered and its conductivity at low temperatures can be increased, thereby improving the low-temperature charge and discharge performance of the battery. At the same time, selecting electrode materials with high specific surface area and good conductivity can accelerate the transmission of sodium ions, reduce side reactions at the electrode / electrolyte interface, and improve the cycle stability and safety of the battery. In addition, the development of new electrode materials, such as hard carbon, sodium titanate, etc., which exhibit excellent electrochemical properties at low temperatures, also provides new possibilities for the application of sodium-ion batteries in extreme environments.
[0004] Despite this, most low-temperature sodium-ion batteries on the market can only discharge in low-temperature environments, and the discharge capacity is relatively low, far from meeting actual needs. More importantly, these batteries have not yet achieved the charging function in low-temperature environments, which seriously limits the widespread application of sodium-ion batteries in cold regions. Summary of the invention
[0005] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a low-temperature sodium ion battery that can achieve excellent charge and discharge performance under low temperature conditions.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A low-temperature sodium ion battery comprises an electrolyte and a positive electrode, a glue-coated separator and a negative electrode stacked in sequence, wherein the electrolyte comprises the following raw materials in parts by mass: 0.5-1.0 parts of NaFP6, 0.3-0.8 parts of NaFSI, 0.5-1.5 parts of vinylene carbonate, 1-3 parts of fluoroethylene carbonate, 1-2 parts of ethylene sulfate, 0.5-1.5 parts of 1,3-propane sultone, 0.5-1.5 parts of sodium difluorooxalatoborate, 0.5-1.5 parts of triborate and 2-5 parts of an organic solvent.
[0008] The present invention can effectively reduce the viscosity of the electrolyte by 1,3-propane sultone, thereby maintaining a high ionic conductivity at low temperatures. Secondly, the melting point of the electrolyte can be significantly reduced by using organic solvents and NaFSI and NaFP6, ensuring that the electrolyte remains liquid at extremely low temperatures, ensuring the migration of ions and the transfer of charges. In addition, fluoroethylene carbonate and ethylene sulfate can form a LiF-rich SEI (solid electrolyte interface) film on the electrode surface. This SEI film has a low electronic impedance and a high sodium ion conductivity, which helps to improve the stability of the electrode and the cycle life of the battery. Sodium difluorooxalatoborate can not only form a stable SEI film, but also does not contain hydrofluoric acid, which can increase the charge transfer rate, reduce the polarization of the battery at low temperatures, and further improve the charge and discharge efficiency of the battery. It can be seen that the present invention can significantly improve the physical and chemical properties of the electrolyte by reasonably selecting and proportioning these additives, such as reducing viscosity, reducing freezing point, forming a stable SEI film, etc., so as to work together to improve the performance of the battery in a low temperature environment. This optimized electrolyte design not only improves the battery's discharge capacity and cycle stability under cold conditions, but also significantly improves the battery's overall performance, making it more suitable for application requirements in high altitudes and cold regions.
[0009] In the above-mentioned low-temperature sodium ion battery, the organic solvent includes at least three of dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, ethyl acetate, and ethylene carbonate.
[0010] In the above-mentioned low-temperature sodium ion battery, the positive electrode includes an aluminum foil with a thickness of 12-15um and a positive electrode active material layer coated on the surface of the aluminum foil, and the positive electrode active material includes the following raw materials in mass fractions: 90-96 parts of sodium nickel iron manganese oxide, 0.3-0.8 parts of Ketjen black, 1-1.8 parts of carbon black, 0.5-0.9 parts of carbon nanotubes, and 1.5-2 parts of polyvinylidene fluoride.
[0011] In the above-mentioned low-temperature sodium ion battery, the particle size of sodium nickel iron manganese oxide D50 is 5-6 um.
[0012] In the above-mentioned low-temperature sodium ion battery, the surface density of the positive electrode active material layer coated on the surface of the aluminum foil is 11-13 mg / cm 2 .
[0013] In the above-mentioned low-temperature sodium ion battery, the negative electrode includes a carbon-coated aluminum foil with a thickness of 12-15um and a negative electrode active material layer coated on the surface of the carbon-coated aluminum foil, and the negative electrode active material includes the following components in mass percentage: 94-96 parts of hard carbon, 0.3-0.5 parts of Ketjen black, 1-1.5 parts of carbon black, 0.5-0.6 parts of carbon nanotubes, 1.5-1.8 parts of polyvinylidene fluoride, 1-1.3 parts of styrene-butadiene rubber, and 0.5-1.5 parts of polyacrylic acid.
[0014] Preferably, the hard carbon D50 particle size is 3-8 um.
[0015] In the above-mentioned low-temperature sodium ion battery, the surface density of the negative electrode active material layer coated on the surface of the carbon-coated aluminum foil is 6-8 mg / cm 2 .
[0016] The present invention controls the surface density of the positive electrode and the negative electrode, which is mainly reflected in the following aspects: First, a lower surface density means a thinner pole piece, which can not only directly reduce the diffusion distance of sodium ions in the electrode material, but also improve the distribution and infiltration of the electrolyte in the electrode, which helps to improve the ionic conductivity of the electrolyte, thereby reducing the internal resistance of the battery and improving the charging and discharging efficiency of the battery, especially under low temperature conditions. Secondly, a thin pole piece helps to reduce the polarization phenomenon of the battery at low temperatures, because the migration path of the sodium ions in the electrode material becomes shorter and the internal resistance of the battery is also smaller, thereby improving the low-temperature discharge capacity and cycle stability of the battery. Finally, a lower surface density means less active material, thereby reducing the damage to the material structure caused by the cyclic deintercalation of sodium ions, especially under low temperature conditions, the cyclic deintercalation of sodium ions may cause greater damage to the material structure. Through these measures, the present invention significantly improves the performance and reliability of sodium ion batteries in low temperature environments.
[0017] In the above-mentioned low-temperature sodium ion battery, the diaphragm is a glue-coated diaphragm with a thickness of 10-15 um.
[0018] In the above-mentioned low-temperature sodium ion battery, the glue-coated diaphragm is composed of an oily PVDF layer, a polypropylene layer, a ceramic layer, and an oily PVDF layer from the inside to the outside, wherein the thickness ratio of the oily PVDF layer, the polypropylene layer, the ceramic layer, and the oily PVDF layer is 0.5-1.5:5-15:1-3:0.5-1.5.
[0019] Preferably, the thicknesses of the oily PVDF layer, the polypropylene layer, the ceramic layer, and the oily PVDF layer are 0.5-1.5um, 5-15um, 1-3um, and 0.5-1.5um, respectively.
[0020] The adhesive-coated diaphragm of the present invention helps to improve the adhesion between the diaphragm and the organic matter in the electrode, improves the contact ability between the positive and negative electrodes and the diaphragm, shortens the transmission channel of sodium ions, greatly reduces polarization, and thus improves the low-temperature performance of the battery. In addition, the ceramic in the diaphragm enhances the puncture resistance of the diaphragm, preventing short circuits caused by sodium dendrites piercing the diaphragm during long-term battery cycles.
[0021] The present invention also provides a method for preparing the above-mentioned low-temperature sodium ion battery, the method comprising the following steps:
[0022] S1, forming a battery cell by stacking the positive electrode sheet, the negative electrode sheet and the separator in a Z-shaped manner;
[0023] S2, then ultrasonically weld the positive electrode tab and the negative electrode tab on the positive electrode sheet and the negative electrode sheet respectively, and place the battery cell in an aluminum-plastic film shell for baking;
[0024] S3. Then inject electrolyte into the battery cell, seal it and let it stand, then chemically divide it into different capacities, and finally age it to obtain a sodium ion battery.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention significantly shortens the transmission channel of ions between the electrode and the electrolyte, significantly enhances the contact between the electrode and the diaphragm, reduces the interface resistance, improves the low-temperature cycle performance of the battery, and prolongs the service life of the battery by controlling the electrolyte and the positive electrode, the diaphragm and the negative electrode stacked in sequence.
[0027] 2. The present invention introduces superconducting carbon black Ketjen black into the positive and negative electrodes, which can form a conductive network with the active material, promote the transmission and storage of electrons, and thus reduce the internal resistance of the electrode; the porous structure of carbon black can serve as a support for the active material, increase the specific surface area of the electrode, and improve the contact area between the electrolyte and the electrode material.
[0028] 3. The present invention uses a low-temperature electrolyte to increase the transmission speed of electrons and ions inside the battery under cold conditions, so that the battery has better charge and discharge performance at -20°C, and the sodium ion battery can exhibit excellent kinetic characteristics in a low-temperature environment, which makes their performance under a wide temperature range very outstanding, and promotes the commercial application of sodium ion batteries in low-temperature environments. DETAILED DESCRIPTION
[0029] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.
[0030] Embodiment 1:
[0031] S1. Prepare the electrolyte raw materials according to the following mass parts: 0.7 parts of NaFP6, 0.5 parts of NaFSI, 1 part of vinylene carbonate, 2 parts of fluoroethylene carbonate, 1.5 parts of ethylene sulfate, 1 part of 1,3-propane sultone, 1 part of sodium difluorooxalatoborate, 1 part of triborate and 3 parts of organic solvent.
[0032] The organic solvent is ethyl methyl carbonate, propylene carbonate and ethyl acetate in a mass ratio of 1:1:1.
[0033] S2, NaFP 6、 NaFSI and an organic solvent are mixed in a reaction vessel, and then the remaining raw materials are added and stirred and mixed continuously, and finally argon gas is used for protection;
[0034] S3, prepare the positive electrode active material raw materials according to the following mass parts: 95.5 parts of sodium nickel iron manganese oxide with a D50 particle size of 5 um, 0.6 parts of Ketjen black, 1.4 parts of carbon black, 0.7 parts of carbon nanotubes, and 1.8 parts of polyvinylidene fluoride;
[0035] S4: Sodium nickel iron manganese oxide, Ketjen black, carbon black, carbon nanotubes and polyvinylidene fluoride are mixed into a slurry and evenly coated on an aluminum foil with a thickness of 13 μm. The coating surface density is 12 mg / cm 2 After drying, rolling and cutting, the positive electrode sheet is obtained;
[0036] S5. Prepare the negative electrode active material raw materials according to the following mass proportions: 94.2 parts of hard carbon with a D50 particle size distribution of 5 um, 0.4 parts of Ketjen black, 1.1 parts of carbon black, 0.55 parts of carbon nanotubes, 1.65 parts of polyvinylidene fluoride, 1.1 parts of styrene-butadiene rubber, and 1.0 parts of polyacrylic acid.
[0037] S6. Mix hard carbon, Ketjen black, carbon black, carbon nanotubes, polyvinylidene fluoride and styrene-butadiene rubber into a slurry, and evenly coat it on a 13 μm thick carbon-coated aluminum foil. The coating surface density is 7 mg / cm 2 After drying, rolling and cutting, a negative electrode sheet is obtained;
[0038] S7, forming a battery cell by stacking the positive electrode sheet, the negative electrode sheet and the glue-coated separator in a Z-shaped manner, and then ultrasonically welding the positive electrode tab and the negative electrode tab on the positive electrode sheet and the negative electrode sheet, respectively, and finally placing the battery cell in an aluminum-plastic film shell and baking at 90° C. to remove moisture from the battery cell;
[0039] The glue-coated diaphragm is composed of an oily PVDF layer, a polypropylene layer, a ceramic layer, and an oily PVDF layer from the inside to the outside, wherein the thickness of the oily PVDF layer, the polypropylene layer, the ceramic layer, and the oily PVDF layer are 1um, 9um, 2um, and 1um, respectively;
[0040] S8. Inject 7 g / mAh electrolyte into the battery cell, seal it and let it stand, convert the obtained battery cell into different capacities, and age it for 24 hours to obtain a sodium ion battery.
[0041] Embodiment 2:
[0042] S1. Prepare the electrolyte raw materials according to the following mass parts: 0.5 parts of NaFP6, 0.3 parts of NaFSI, 0.5 parts of vinylene carbonate, 1 part of fluoroethylene carbonate, 1 part of ethylene sulfate, 0.5 parts of 1,3-propane sultone, 0.5 parts of sodium difluorooxalatoborate, 0.5 parts of triborate and 2 parts of organic solvent.
[0043] The organic solvent is ethyl methyl carbonate, propylene carbonate and ethyl acetate in a mass ratio of 1:1:1.
[0044] S2, NaFP 6、 NaFSI and an organic solvent are mixed in a reaction vessel, and then the remaining raw materials are added and stirred and mixed continuously, and finally argon gas is used for protection;
[0045] S3, prepare the positive electrode active material raw materials according to the following mass parts: 90 parts of sodium nickel iron manganese oxide with a D50 particle size of 5 um, 0.3 parts of Ketjen black, 1 part of carbon black, 0.5 parts of carbon nanotubes, and 1.5 parts of polyvinylidene fluoride;
[0046] S4: Sodium nickel iron manganese oxide, Ketjen black, carbon black, carbon nanotubes and polyvinylidene fluoride are mixed into a slurry and evenly coated on an aluminum foil with a thickness of 13 μm. The coating surface density is 12 mg / cm 2 After drying, rolling and cutting, the positive electrode sheet is obtained;
[0047] S5. Prepare the negative electrode active material raw materials according to the following mass proportions: 94 parts of hard carbon with a D50 particle size distribution of 5 um, 0.3 parts of Ketjen black, 1 part of carbon black, 0.5 parts of carbon nanotubes, 1.5 parts of polyvinylidene fluoride, 1 part of styrene-butadiene rubber, and 0.5 parts of polyacrylic acid.
[0048] S6. Mix hard carbon, Ketjen black, carbon black, carbon nanotubes, polyvinylidene fluoride, and styrene-butadiene rubber into a slurry, and evenly coat it on a 13 μm thick carbon-coated aluminum foil. The coating surface density is 7 mg / cm 2 After drying, rolling and cutting, a negative electrode sheet is obtained;
[0049] S7, forming a battery cell by stacking the positive electrode sheet, the negative electrode sheet and the glue-coated separator in a Z-shaped manner, and then ultrasonically welding the positive electrode tab and the negative electrode tab on the positive electrode sheet and the negative electrode sheet, respectively, and finally placing the battery cell in an aluminum-plastic film shell and baking at 90° C. to remove moisture from the battery cell;
[0050] The glue-coated diaphragm is composed of an oily PVDF layer, a polypropylene layer, a ceramic layer, and an oily PVDF layer from the inside to the outside, wherein the thickness of the oily PVDF layer, the polypropylene layer, the ceramic layer, and the oily PVDF layer are 1um, 9um, 2um, and 1um, respectively;
[0051] S8. Inject 7 g / mAh electrolyte into the battery cell, seal it and let it stand, convert the obtained battery cell into different capacities, and age it for 24 hours to obtain a sodium ion battery.
[0052] Embodiment 3:
[0053] S1. Prepare electrolyte raw materials according to the following mass parts: 1.0 part NaFP6, 0.8 part NaFSI, 1.5 parts vinylene carbonate, 3 parts fluoroethylene carbonate, 2 parts ethylene sulfate, 1.5 parts 1,3-propane sultone, 1.5 parts sodium difluorooxalatoborate, 1.5 parts triborate and 5 parts organic solvent.
[0054] The organic solvent is ethyl methyl carbonate, propylene carbonate and ethyl acetate in a mass ratio of 1:1:1.
[0055] S2, NaFP 6、 NaFSI and an organic solvent are mixed in a reaction vessel, and then the remaining raw materials are added and stirred and mixed continuously, and finally argon gas is used for protection;
[0056] S3, prepare the positive electrode active material raw materials according to the following mass parts: 96 parts of sodium nickel iron manganese oxide with a D50 particle size of 5 um, 0.8 parts of Ketjen black, 1.8 parts of carbon black, 0.9 parts of carbon nanotubes, and 2 parts of polyvinylidene fluoride;
[0057] S4: Sodium nickel iron manganese oxide, Ketjen black, carbon black, carbon nanotubes and polyvinylidene fluoride are mixed into a slurry and evenly coated on an aluminum foil with a thickness of 13 μm. The coating surface density is 12 mg / cm 2 After drying, rolling and cutting, the positive electrode sheet is obtained;
[0058] S5. Prepare the negative electrode active material raw materials according to the following mass parts: 96 parts of hard carbon with a D50 particle size distribution of 5 um, 0.5 parts of Ketjen black, 1.5 parts of carbon black, 0.6 parts of carbon nanotubes, 1.8 parts of polyvinylidene fluoride, 1.3 parts of styrene butadiene rubber, and 1.5 parts of polyacrylic acid.
[0059] S6. Mix hard carbon, Ketjen black, carbon black, carbon nanotubes, polyvinylidene fluoride, and styrene-butadiene rubber into a slurry, and evenly coat it on a 13 μm thick carbon-coated aluminum foil. The coating surface density is 7 mg / cm 2 After drying, rolling and cutting, a negative electrode sheet is obtained;
[0060] S7, forming a battery cell by stacking the positive electrode sheet, the negative electrode sheet and the glue-coated separator in a Z-shaped manner, and then ultrasonically welding the positive electrode tab and the negative electrode tab on the positive electrode sheet and the negative electrode sheet, respectively, and finally placing the battery cell in an aluminum-plastic film shell and baking at 90° C. to remove moisture from the battery cell;
[0061] The glue-coated diaphragm is composed of an oily PVDF layer, a polypropylene layer, a ceramic layer, and an oily PVDF layer from the inside to the outside, wherein the thickness of the oily PVDF layer, the polypropylene layer, the ceramic layer, and the oily PVDF layer are 1um, 9um, 2um, and 1um, respectively;
[0062] S8. Inject 7 g / mAh electrolyte into the battery cell, seal it and let it stand, convert the obtained battery cell into different capacities, and age it for 24 hours to obtain a sodium ion battery.
[0063] Embodiment 4:
[0064] The only difference from Example 1 is that the organic solvent is only ethyl methyl carbonate.
[0065] Embodiment 5:
[0066] The only difference from Example 1 is that the organic solvents are only ethyl methyl carbonate and propylene carbonate.
[0067] Embodiment 6:
[0068] The only difference from Example 1 is that the raw materials of the positive electrode and negative electrode active materials do not contain Ketjen black.
[0069] Embodiment 7:
[0070] The only difference from Example 1 is that the surface density of the positive electrode active material layer coated on the surface of the aluminum foil is 5 mg / cm 2 The surface density of the negative electrode active material layer on the surface of the carbon-coated aluminum foil is 3 mg / cm 2 .
[0071] Embodiment 8:
[0072] The only difference from Example 1 is that the surface density of the positive electrode active material layer coated on the surface of the aluminum foil is 20 mg / cm 2 The surface density of the negative electrode active material layer on the surface of the carbon-coated aluminum foil is 15 mg / cm 2 .
[0073] Embodiment 9:
[0074] The only difference from Example 1 is that the diaphragm is a conventional ceramic diaphragm (ceramic diaphragm\135\boehmite\9+3\Xuran-Neumi\PE).
[0075] Embodiment 10:
[0076] The only difference from Example 1 is that the particle size of sodium nickel iron manganate D50 is 10 um.
[0077] Comparative Example 1:
[0078] The only difference from Example 1 is that the electrolyte raw material does not contain NaFP6.
[0079] Comparative Example 2:
[0080] The only difference from Example 1 is that the electrolyte raw material does not contain NaFSI.
[0081] Comparative Example 3:
[0082] The only difference from Example 1 is that the electrolyte raw material does not contain vinylene carbonate.
[0083] Comparative Example 4:
[0084] The only difference from Example 1 is that the electrolyte raw material does not contain ethylene sulfate.
[0085] Comparative Example 5:
[0086] The only difference from Example 1 is that the electrolyte raw material does not contain 1,3-propane sultone.
[0087] Performance testing:
[0088] (1) Energy density test:
[0089] The sodium ion batteries prepared in Examples 1-12 and Comparative Examples 1-5 were placed in a 25°C thermostat for 24 hours, then charged to 3.9 V at 0.2C constant current, then left to stand for 30 minutes, and discharged to 1.5 V at 0.5C. The energy obtained by the discharge divided by the mass of the battery is the energy density of the battery.
[0090] (2) -20℃ low temperature discharge performance test:
[0091] The sodium ion batteries prepared in Examples 1-12 and Comparative Examples 1-5 were placed in a -20°C thermostat for 24 hours, then charged to 3.9 V at 0.2C constant current, then left to stand for 30 minutes, and discharged to 1.5 V at 0.5C. The capacity obtained by the discharge divided by the mass of the positive electrode activity is the gram capacity of the -20°C low-temperature discharge.
[0092] (3) Cycle life test:
[0093] The sodium ion batteries prepared in Examples 1-12 and Comparative Examples 1-5 were placed in a -20°C thermostat and allowed to stand for 24 hours, then charged to 3.9V at 0.2C constant current, then allowed to stand for 30 minutes, discharged to 1.5V at 0.5C, allowed to stand for 30 minutes, and continued to follow the above charging steps, repeating this process.
[0094] Table 1: Performance test results of sodium ion batteries prepared in Examples 1-12 and Comparative Examples 1-5
[0095]
[0096] In summary, the present invention significantly shortens the transmission channel of ions between the electrode and the electrolyte, significantly enhances the contact between the electrode and the diaphragm, reduces the interface resistance, improves the low-temperature cycle performance of the battery, and extends the service life of the battery by controlling the electrolyte and the positive electrode, diaphragm and negative electrode stacked in sequence.
[0097] The parts of the embodiments herein that are not exhaustive of the midpoint values of the technical scope claimed for protection by the present invention and the new technical solutions formed by equivalent replacement of single or multiple technical features in the technical solutions of the embodiments are also within the scope claimed for protection by the present invention; at the same time, in all the listed or unlisted embodiments of the scheme of the present invention, each parameter in the same embodiment merely represents an example of its technical solution (i.e., a feasible solution), and there is no strict coordination and limitation relationship between the parameters, wherein the parameters can be replaced with each other without violating the axioms and the claims of the present invention, unless otherwise stated.
[0098] The technical means disclosed in the scheme of the present invention are not limited to the technical means disclosed in the above technical means, but also include technical schemes composed of any combination of the above technical features. The above is a specific implementation of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also regarded as the protection scope of the present invention.
[0099] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A low-temperature sodium ion battery, characterized in that: The low-temperature sodium ion battery comprises an electrolyte and a positive electrode, a glue-coated separator and a negative electrode stacked in sequence, wherein the electrolyte comprises the following raw materials in parts by mass: 0.5-1.0 parts of NaFP6, 0.3-0.8 parts of NaFSI, 0.5-1.5 parts of vinylene carbonate, 1-3 parts of fluoroethylene carbonate, 1-2 parts of ethylene sulfate, 0.5-1.5 parts of 1,3-propane sultone, 0.5-1.5 parts of sodium difluorooxalatoborate, 0.5-1.5 parts of triborate and 2-5 parts of an organic solvent.
2. A low-temperature sodium ion battery according to claim 1, characterized in that: The organic solvent includes at least three of dimethyl carbonate, ethyl methyl carbonate, ethyl methyl carbonate, propylene carbonate, ethyl acetate, and ethylene carbonate.
3. A low-temperature sodium ion battery according to claim 1, characterized in that: The positive electrode comprises an aluminum foil with a thickness of 12-15 μm and a positive electrode active material layer coated on the surface of the aluminum foil, wherein the positive electrode active material comprises the following raw materials in parts by mass: 90-96 parts of sodium nickel iron manganese oxide, 0.3-0.8 parts of Ketjen black, 1-1.8 parts of carbon black, 0.5-0.9 parts of carbon nanotubes, and 1.5-2 parts of polyvinylidene fluoride.
4. A low-temperature sodium ion battery according to claim 3, characterized in that: The particle size of sodium nickel iron manganate D50 is 5-6um.
5. A low-temperature sodium ion battery according to claim 3, characterized in that: The surface density of the positive electrode active material layer coated on the aluminum foil surface is 11-13 mg / cm 2 .
6. A low-temperature sodium ion battery according to claim 1, characterized in that: The negative electrode comprises a carbon-coated aluminum foil with a thickness of 12-15 μm and a negative electrode active material layer coated on the surface of the carbon-coated aluminum foil. The negative electrode active material comprises the following components by mass percentage: 94-96 parts of hard carbon, 0.3-0.5 parts of Ketjen black, 1-1.5 parts of carbon black, 0.5-0.6 parts of carbon nanotubes, 1.5-1.8 parts of polyvinylidene fluoride, 1-1.3 parts of styrene-butadiene rubber, and 0.5-1.5 parts of polyacrylic acid.
7. A low-temperature sodium ion battery according to claim 6, characterized in that: The surface density of the negative electrode active material layer coated on the surface of the carbon-coated aluminum foil is 6-8 mg / cm 2 .
8. A low-temperature sodium ion battery according to claim 1, characterized in that: The diaphragm is a rubber-coated diaphragm with a thickness of 10-15um.
9. A low-temperature sodium ion battery according to claim 1, characterized in that: The glue-coated diaphragm is composed of an oily PVDF layer, a polypropylene layer, a ceramic layer, and an oily PVDF layer from the inside to the outside, wherein the thickness ratio of the oily PVDF layer, the polypropylene layer, the ceramic layer, and the oily PVDF layer is 0.5-1.5: 5-15: 1-3: 0.5-1.
5.
10. A method for preparing a low-temperature sodium ion battery as claimed in claim 1, characterized in that: The method comprises the following steps: S1, forming a battery cell by stacking the positive electrode sheet, the negative electrode sheet and the separator in a Z-shaped manner; S2, then ultrasonically weld the positive electrode tab and the negative electrode tab on the positive electrode sheet and the negative electrode sheet respectively, and place the battery cell in an aluminum-plastic film shell for baking; S3. Then inject electrolyte into the battery cell, seal it and let it stand, then chemically divide it into different capacities, and finally age it to obtain a sodium ion battery.
Citation Information
Patent Citations
Sodium ion battery
CN116031488A
Electrolyte for ultralow-temperature lithium battery and preparation method of electrolyte
CN116365028A
Sodium-ion battery electrolyte containing film-forming additive and sodium-ion battery
CN117154217A
Sodium battery electrolyte and sodium ion battery
CN117276659A
Non-aqueous electrolyte compositions
US20250023104A1
Cited By
Low-temperature sodium ion electrolyte and preparation method and application thereof
CN120527452A